A Bibliometric Analysis of Chatbot Implementation - Agus, Taufiq; Siti Mujanah; Fianto, Achmad Yanu Alif (PT Inovasi Pratama Internasional, 2025)
The use of artificial intelligence (AI)-based technology is increasingly widespread. This includes the use of chatbots. Chatbots are used in various sectors including education, health, and technology. This study aims to analyze research related to chatbots in the 2022-2024 period. The research method used is a bibliometric analysis approach. Collection of articles from Google Scholar using Harzing's Publish or Perish software and analysis using VOSviewer software. The word